Regional Scenario of Global Suicide .......... IJMTFM (2011) 1(1): 6-11 - S.N, Vijayamahantesh; M.R, Anitha; G.M, Raju (International Journal of Medical Toxicology and Forensic Medicine, 2012)
Suicide is a serious public health problem. The World Health Organization (WHO) has recognizing the growing problem of suicide worldwide, urged member nations to address the phenomenon. As suicides continue to be a major burden , study of suicide is conducted over a period of 2-years that is from 1st January 2003 to 31st December 2004. The psychological autopsy conducted, which have been reported in mortuary, here show clear evidence that most of poisonings were by Poisoning & Hanging. And most of victims were suffering from Physical and Psychiatric illness. Majority were illiterates and agriculturists. The special emphasis was made on time of committing suicide, which shows that 68.90% were day time only.